THE EFFECTIVENESS OF TONGUE TWISTERS STARTEGY TOWARD STUDENTS' SPEAKING ABILITY - Intan Yayang Shafika (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The aim of this study is to identify the problems of students at MA Muhammadiyah Purbolinggo, especially for speaking,. The subjects were 40 students at 11th grade of MA Muhammadiyah Purbolinggo. This research employed quasi- experimentnal research design. There were two varibales: independent variable is Tongue Twister Strategy and the depent variable is Speaking Ability. The pre-test result of mean score of control group which was lower than experimental group (46.20 > 39.60). In post-test. the mean score of control group was found to be also lower than experimental group (72.20 > 58.40). From the data, the researcher concluded that there was an effectiveness in using tongue twister to improve students’ speaking ability at MA Muhammadiyah Purbolinggo. that the significance level 0,05, tobserved (7.627) is higher than ttable (2,024). Therefore, the Alternative Hypothesis or Ha is accepted which means there is significant effect of Tongue Twister on speaking skill of students, and it can be concluded that the research question has been answered.